"God is the creator of all life and the energy of this world": German intersex Christians' reflection on the image of God and being created in God's image. Issue 2 (4th May 2018) - Budwey, Stephanie A.
ABSTRACT: Intersex individuals are often told they are not human beings because they do not neatly fit into the categories of "female" and "male." Many are made to feel like monsters. Christianity enforces this model of sexual dimorphism with the notion that to be a human being means to be created clearly "female" or clearly "male" in the image of God. This paper draws on interviews with German intersex Christians to explore their diverse images of God and what it means to be created in God's image with the goal of creating new "conditions of possibility" that represent the full range of human sex/gender.